An innovative 3D-CFD-approach towards virtual development of internal combustion engines - Chiodi, Marco; Rimondini, Michela; SpringerLink (Online service). (Wiesbaden Vieweg+Teubner, 2011)
In the engine development process, simulation and predictive programs have continuously gained in reliance. Due to the complexity of future internal combustion engines the application of simulation programs towards a reliable ?virtual engine development? is a need that represents one of the greatest challenges. Marco Chiodi presents an innovative 3D-CFD-tool, exclusively dedicated and optimized for the simulation of internal combustion engines. Thanks to improved or newly developed 3D-CFD-models for the description of engine processes, this tool ensures an efficient and reliable calculation also by using coarse 3D-CFD-meshes. Based on this approach the CPU-time can be reduced up to a factor 100 in comparison to traditional 3D-CFD-simulations. In addition an integrated and automatic ?evaluation tool? establishes a comprehensive analysis of the relevant engine parameters. Due to the capability of a reliable ?virtual development? of full-engines, this fast response 3D-CFD-tool makes a major contribution to the engine development process.
Simulation of Internal Combustion Engines; Engine Energy-Balance; Real Working-Process Analysis; One-Dimension Simulation (1D-CFD-Simulation); Three-Dimensional Simulation (3D-CFD-Simulation); Towards an improved 3D-CFD-Simulation; 3D-CFD-Modeling of the Thermodynamic Properties of the Working Fluid; 3D-CFD-Modeling of the Combustion for SI-Engines; 3D-CFD-Modeling of the Wall Heat-Transfer; A Way towards Virtual Engine Development
Electronic reproduction.
Keywords: Internal combustion engines -- Design and construction -- Computer simulation; Economics/Management science; Automotive engineering; Electronic books